A Study of the Social and Environmental Conditions of Slum Settlement Areas in Tanete Village - Hasniar Baharuddin; Puspita Utari (Journal Of Architectural Design & Technology, 2025)
Slum settlements remain an environmental and social issue that is still widely found, including in rural areas. Tanete Village is one of the areas that shows indications of slum settlements, characterized by limited infrastructure and facilities, low housing quality, and inadequate environmental conditions. This study aims to examine the social and environmental conditions of slum settlement areas in Tanete Village. The analysis focuses on the social characteristics of the community, the physical condition of housing, the availability of basic infrastructure, and the overall quality of the residential environment. The research method employed is a descriptive approach, with data collected through field observations, interviews with local residents, and documentation. The results indicate that the slum conditions in Tanete Village are influenced by housing density, limited access to clean water and sanitation, and a low level of environmental awareness among the community. In addition, social factors such as income levels and livelihood patterns also play a role in shaping settlement conditions. This study is expected to serve as a reference for the government and relevant stakeholders in formulating strategies for settlement arrangement and improving the quality of residential areas in Tanete Village.